2021
DOI: 10.3389/fendo.2021.724853
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Embryo Storage Time on Pregnancy and Perinatal Outcomes and the Time Limit of Vitrification: A Retrospective Cohort Study

Abstract: BackgroundThe technique of embryo cryopreservation has been increasingly applied in clinical settings. However, there has been a concern about the safety and efficacy of long-term freezing of embryos. Therefore, the aim of this study was to evaluate whether storage time of vitrification had any effects on pregnancy as well as perinatal outcomes, further, to explore the appropriate time limit of vitrification.MethodsThe study included women who underwent at least one frozen-thawed cycle with single embryo trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Wirleitner et al demonstrated that the cryopreservation storage time has no effect on blastocyst survival and pregnancy outcomes when these blastocysts are stored in the LN 2 tank for up to 6 years [ 11 ]. In contrast, Cui et al showed that the live birth and clinical pregnancy rates decreased significantly when the storage time exceeded 5 years [ 24 ]; however, the sample size of these three studies was small. Recently, two large retrospective analyses showed that the prolonged storage time was negatively associated with pregnancy and live birth [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wirleitner et al demonstrated that the cryopreservation storage time has no effect on blastocyst survival and pregnancy outcomes when these blastocysts are stored in the LN 2 tank for up to 6 years [ 11 ]. In contrast, Cui et al showed that the live birth and clinical pregnancy rates decreased significantly when the storage time exceeded 5 years [ 24 ]; however, the sample size of these three studies was small. Recently, two large retrospective analyses showed that the prolonged storage time was negatively associated with pregnancy and live birth [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a decrease in DMSO-induced ATP might cause downstream effects that may disrupt cellular function, fetal development, and implantation potential [ 72 , 73 , 74 , 75 ]. Finally, over the past few years, several reports have shown the detrimental effects of cryopreservation programs on the epigenetic makeup of the embryo, protein expression, and DNA integrity [ 76 , 77 , 78 , 79 , 80 ], as well as alteration of such genes involved in critical biological processes [ 79 , 80 , 81 ], inducing an increase in free radical production and apoptosis [ 81 , 82 , 83 , 84 , 85 ].…”
Section: Potential Damaging Effects Of Cryopreservationmentioning
confidence: 99%
“…These cryoprotectants might affect embryo metabolism, such as protein expression, DNA integrity, and cytoskeletal and nuclear structures 87–90 . A few studies have suggested that CPAs might be linked to epigenetic aberration in oocytes and embryos, and these alterations could be transmitted to future generations 91,92 . Thus, since cryopreservation has become widely used in ART and other fields such as regenerative and transplantation medicine, it is critical to examine potentially genomic and epigenetic changes associated with the current technique.…”
Section: Concerns Related To Cryopreservation and Cryoprotectantsmentioning
confidence: 99%
“…[87][88][89][90] A few studies have suggested that CPAs might be linked to epigenetic aberration in oocytes and embryos, and these alterations could be transmitted to future generations. 91,92 Thus, since cryopreservation has become widely used in ART and other fields such as regenerative and transplantation medicine, it is critical to examine potentially genomic and epigenetic changes associated with the current technique. Further epidemiological studies performed on a large scale are necessary to evaluate the implications of the cryopreservation process and the use of CPAs on the health and well-being of the offspring not only at the time of delivery but also during later adult life.…”
Section: Concerns Related To Cryopreservation and Cryoprotectantsmentioning
confidence: 99%